2011
DOI: 10.1111/j.1526-4637.2011.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Field Stimulation for Chronic Pain: 100 Cases and Review of the Literature

Abstract: This prospective 100 consecutive PNFS patient outcome study demonstrates that PNFS can be a safe and effective treatment option for, otherwise, intractable chronic pain conditions. PNFS has the potential to fundamentally change the way we think about pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 53 publications
7
85
0
4
Order By: Relevance
“…PNFS has been described in a couple of case reports,58,59,67 smaller cases series,56,62,65 and some studies with higher case numbers 61,64,68. A retrospective multicentre study on 111 patients with chronic low back pain, FBSS, cervical pain, postherpetic neuralgia, tension headache, and some patients with trigeminal neuralgia or thoracic pain showed that the relatively best pain relief was obtained in patients with thoracic back pain, whereas the least pain relief was seen in patients with tension headache.…”
Section: Current Technological Developmentsmentioning
confidence: 97%
“…PNFS has been described in a couple of case reports,58,59,67 smaller cases series,56,62,65 and some studies with higher case numbers 61,64,68. A retrospective multicentre study on 111 patients with chronic low back pain, FBSS, cervical pain, postherpetic neuralgia, tension headache, and some patients with trigeminal neuralgia or thoracic pain showed that the relatively best pain relief was obtained in patients with thoracic back pain, whereas the least pain relief was seen in patients with tension headache.…”
Section: Current Technological Developmentsmentioning
confidence: 97%
“…PNfS has been used for chronic pain with a promising outcome notably in three cases of chronic abdominal pain [7–9]. In this case, she experienced >90% pain reduction from the PNfS therapy during the trial of SCS versus PNfS.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the information is incomplete as neuromodulation for craniofacial pain is frequently a part of bigger studies on pain control. [163] We tried to compare efficacy of different neuromodulation modalities for control of craniofacial pain of different nosology based on ICDH-II classification. [49] Technical and surgical aspects of different neuromodulation techniques are described elsewhere.…”
Section: Methodsmentioning
confidence: 99%